United States Supreme Court Politics: Focus On Steven’s And Other Justices’ Longevity - Zan, Myint (Journal of Malaysian and Comparative Law, 2019)
In the United States Supreme Court politics the month of June is normally "crunch time". Many rulings are delivered by the Supreme Court during and before the end of the month of June. In the beginning of July of each year the nine Justices of the Supreme Court go for a three month (fully-paid of course) summur vacation. After the three months vacation the Court resumes hearing new cases on the ’first Monday in October’.